Hubungan Antara Karakteristik Klinis Pasien TB Paru dengan Gambaran Radiologi CT Scan Thorax - Nurfika Utami; Rahmawati Rahmawati; Bulkis Natsir (Universitas Muhammadiyah Manado, 2023)
Tuberculosis infection is one of the most common and dangerous human infections. Tuberculosis infection is a health problem in which one-third of the world's population is infected with Mycobacterium tuberculosis. The diagnosis of TB is still limited to the results of clinical examination, laboratory examination of BTA sputum and conventional thoracic X-rays. Meanwhile, CT scanning has not yet become a standard modality, due to its high cost and unavailability in many primary health care centres. However, CT scans are considered to have advantages in diagnosing minimal lesions, differentiating active and inactive conditions, assessing endobronchial expansion, and better diagnosing pulmonary TB with negative acid-resistant bacteria (BTA) sputum examination results. The method used was a literature review with a Narrative Review design to identify and summarise previously published articles on the relationship between clinical characteristics of pulmonary TB patients and CT scan radiological images. From the 4 articles summarised, it was found that the large number of variations that are not typical of thoracic CT scans of pulmonary TB patients make the diagnosis of pulmonary TB more complicated. It takes precision and good cooperation between radiologists and clinicians to jointly make a correct diagnosis of pulmonary TB.